The Structural Linguistics Patterns of the Written Component of the Malaysian University English Test (MUET) - Singh, Manvender Kaur Sarjit; Shamsudin, Sarimah; Isam, Hishamuddin; Kaur, Naginder; Singh, Gurmit Singh Pertap; Kanestion, Anita (International Review of Management and Marketing, 2016)
The core of this paper is reflecting actual language use as the ‘performance' of the language learners. The areas of investigation involves examining the structural linguistics patterns used by the language learners while preparing the essays, in terms of using the part-of-speech (POS) and the sentence level syntactical analysis of the most frequently used POS, which reflects the distributional patterns of the linguistic components used. The methodology applied is fundamental as it tends to investigate the linguistic components in the compiled genre-specific corpus. Computer-based syntactical studies are limited as it requires hard work and long hours in order to key-in the data and then there is the complex analytic method of describing the findings. This paper presents steps taken for corpus compilation and moves identification of the written Malaysian University English Test, in short MUET. It comprises a move analysis and a multidimensional analysis conducted using a compiled representative corpus of MUET essays. As a descriptive and a corpus-based study, it explored the written essays produced by ESL learners in three matriculation colleges in Malaysia. Language and language use are commonly analyzed for competence and performance. Competence is best described as the internalized linguistic knowledge as acquired by the learners while the notion of ‘performance' is best defined as the external evidence of language competence. This paper proposes structural linguistics investigations such as frequency analyses, sentence level syntactical analyses, distributional patterns of sentence level linguistic structural patterns and subject-verb agreement analyses reflecting the writers' knowledge of applying their grammatical linguistics knowledge into their written output in various different contexts. Keywords: Education Management; MUET; Performance JEL Classifications: I21, I23